Assessment of multisystem inflammatory syndrome in children related to COVID-19 - Anwar, Sayeeda; Khan, Zohora Jameela; Akhter, Naznin; Farzana, Fatema; Shormin, Zannatul; Kabir, Farzana (International Journal of Contemporary Pediatrics, 2021)
Background: The COVID-19 pandemic has caused devastating diseases worldwide both in children and adults. Subsequently, a serious and novel pediatric condition called children’s multisystem inflammatory syndrome (MIS-C) has emerged and it is important to understand the temporal association between MIS-C and COVID-19. In hyper inflammation syndrome following COVID-19, MIS-C, and multi-organ involvement were documented in the pediatric population. The main goal of this study was to assess the relation of the MIS-C with COVID-19. Methods: This single-center case-control study was conducted at Dhaka medical college hospital (DMCH), Dhaka, Bangladesh. Among 1715 studied population, 227 COVID-19 positive pediatric patients were included in this study. Among them 103 had features of MIS-C in the case group and 124 were in the control group without MIS-C. Results: There were 6% MIS-C patients with COVID-19. The prevalence of male patients was observed in this study. The mean age of the patient group with MIS-C was 7.8±3.12 years. The frequencies of fever 93.3 vs 67.7%, p=0.045; conjunctivitis 75.6% vs 53.2%, p=0.039; rash 47.3% vs 16.1%; arterial hypotension 71.3 vs 12.9%, p=0.058 hypoxemia 80.4% vs 57.2%, p=0.049 and other features were significantly higher in MIS-C patients than the patients without MIS-C. More patients with MIS-C had cardiac abnormalities in our study. Conclusions: MIS-C is an emerging clinical entity and this study was focused on the cases of MIS-C in the pediatric population withCOVID-19. In patients with atypical clinical findings and complaints about COVID-19, MIS-C-like illnesses should be considered.